Telecollaboration in the secondary language classroom: case study of adolescent interaction and pedagogical integration. Issue 3 (2nd April 2016) - Ware, Paige; Kessler, Greg
Abstract : This study builds on research examining the in-school technology practices of adolescent language learners by exploring the patterns of classroom literacy practices that emerge when a telecollaborative project is introduced into a conventional secondary language classroom. We draw on the conceptual frameworks and discourse analytical tools developed by researchers of online communication practices at the post-secondary level and turn this lens to examine how an international online exchange project might contribute to the creation of an in-school learning environment in which adolescents use technology to interact with distally located peers through telecollaboration. The particular contribution of this study is twofold: to offer insight into patterns that characterize the literacy practices that emerge through the introduction of telecollaboration into the learning environment and to document the types of pedagogical decision-making that such projects introduce into the secondary context. Using a case-study design, we explored two central areas: (1) What patterns of interaction emerge in the literacy practices of adolescent students as they build relationships with their intercultural partners? (2) How do teachers address the pedagogical issues that are foregrounded when introducing innovative literacy practices such as telecollaboration into the secondary learning environment? Our premise is that online exchanges might offer a different kind of learning experience that provides opportunities for adolescents to engage with language in ways that do not typically get enacted in conventional language classrooms. Our interest therefore is grounded both in providing a rich, descriptive inventory of how adolescents engage with telecollaboration in the classroom context, as well as in documenting the types of pedagogical issues that are introduced. We offer a linguistically grounded portrait of what constitutes the interactional patterns and pedagogical issues in a classroom learning environment shaped by the introduction of an online intercultural project. Using a case-study approach, therefore, we provide close documentation and analyses of a 15-week, classroom-based telecollaboration project through student transcripts and focal teacher interviews. We conclude with a discussion of the empirical and pedagogical implications associated with integrating telecollaboration into secondary language classroom contexts.